A new wide-bandgap conjugated polymer based on imide-fused benzotriazole for highly efficient nonfullerene polymer solar cells. (November 2018) - Lan, Liuyuan; Cai, Ping; Mai, Yuliang; Hu, Zhicheng; Wen, Wu; Zhang, Jie; Li, Yunchuan; Shi, Huahong; Zhang, Jian
Abstract: A new imide-fused benzotriazole-based conjugated polymer, PBDTS-TzBI, was designed and synthesized via the introduction of alkylthio side chains. The optical, electrochemical and photovoltaic properties of the polymer were well characterized. PBDTS-TzBI exhibits a strong absorption in the range of 400–650 nm with a wide optical bandgap of 1.80 eV and possesses a deep-lying highest occupied molecular orbital energy level of −5.39 eV. Additive-free non-fullerene polymer solar cell (PSC) devices employing PBDTS-TzBI as electron donor and ITIC-Th as electron acceptor delivered an outstanding power conversion efficiency of 9.67% with a high open-circuit voltage of 0.91 V, which is among the best ITIC-Th-based non-fullerene PSC devices so far. This work indicates that the copolymer PBDTS-TzBI is a very promising alternative polymeric donor for highly efficient non-fullerene polymer solar cells. Graphical abstract: A new alkylthio-substituted copolymer based on imide-fused benzotriazole was developed for additive-free nonfullerene polymer solar cells with a PCE of 9.67%. Image 1 Highlights: A new alkylthio-substituted polymer based on imide-fused benzotriazole has been designed and synthesized. The optical, electrochemical and photovoltaic properties of the polymer were characterized. Nonfullerene polymer solar cells delivered an outstanding power conversion efficiency of 9.67%. The photovoltaic performances were obtained without any solvent additives.